Designing a Web-based Drug Sales Information System at the Jayatri Pharmacy - Yulia Shantika Sari; Lela Adhari; Yopi Nugraha; Dr Tetep (RISTEC : Research in Information Systems and Technology, 2020)
Abstract: Jayatri Pharmacy is one of the pharmacies located in Blubur Limbangan District, this pharmacy distributes pharmaceutical services regarding employment such as drug compounding, drug preparation, drug procurement, drug storage, distribution and delivery of drugs, and providing data or information to the public about pharmacy requirements. At this time, Jayatri Pharmacy is still managed with manual or semi-manual systems. Meanwhile, current needs demand more effective and efficient management. In order to respond to these problems, it can be concluded that a web-based information system can help these pharmacies and their management become more effective and can increase sales turnover. Keywords: Information Systems; Sales; Pharmacy; Drug Abstrak: Apotek Jayatri merupakan salah satu Apotek yang terletak di Kecamatan Blubur Limbangan, Apotek ini membagikan pelayanan kefarmasian mengenai ketenagakerjaan seperti peracikan obat, penyiapan obat, pengadaan obat, penyimpanan obat , pendistribusian serta penyerahan obat, dan memberikan data atau informasi kepada masyarakat tentang syarat Apotek. Pada saat ini Apotek Jayatri masih dijumpai pengelolaan dengan sistem manual atau semi manual. Sedangkan kebutuhan dikala ini menuntut pengelolaan yang lebih efektif dan efisien. Guna menanggapi masalah tersebut, maka dapat disimpulkan bahwa sistem informasi berbasis web dapat membantu terhadap Apotek tersebut dan pengelolaannya menjadi lebih efektif serta dapat meningkatkan omset penjualan. Kata kunci: Sistem Informasi; Penjualan; Apotek; Obat